Synergistic Stereoselective Organocatalysis with Indium(III) Salts - Gualandi, Andrea; Mengozzi, Luca; Wilson, Claire Margaret; Cozzi, Pier Giorgio (Synthesis, 2014)
The compatibility of indium(III) Lewis acids with water and amines allows their employment in synergistic and cooperative catalysis. Stereoselective organocatalytic SN1-type reactions, in which carbenium ions are generated, are promoted by the presence of indium salts. The peculiar properties of indium salts can be exploited in organocatalysis for the design of water-compatible, benign, green processes. The development of such indium(III)-promoted organocatalytic procedures is the focus of our recent research, a summary of which is presented in this article.
Keywords: organocatalysis; stereoselective; amine catalysis; enamine-mediated catalysis; indium(III)